Kapitał duchowy w doskonaleniu zarządzania przedsiębiorstwem - Zymonik, Zofia (Spiritual Capital in Improving Management of an Organization, 2008)
The work presents the concept of spiritual capital in which one proves that the personnel of an enterprise does not consist of economic living beings but people who think about the aim and sense of life. Contemporary business is characterized by non-balance. Constant pursuit of profit by companies not only damages nature in its wide meaning but it also contributes to deepening social inequalities. But it is possible to increase the profit of companies by making good for environment. It requires holistic approach to the system of motivating personnel, open not only for body and mind but also for spirit. Unleashing appropriate motivation and passion in employees is the role of so-called spiritual leaders what this work shows. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 327-338